Empathy as speech manipulation target in pre-election discourse of great britain. - Anna Antonova, (Penerbit UKM, 2011)
Nowadays much attention in linguistics is paid to the study of manipulative kinds of texts which function within the political discourse. This paper deals with the linguistic means that the British political leaders use to actualize empathy and compassion. Despite the basic statements of Darwin’s theory these manipulation targets are considered to be the important mechanisms of tribal human behavior by many ethologists. The pre-election speeches of the British political leaders taken as linguistic data are regarded in the article with the help of intentional analysis and the analysis of stylistic means and vocabulary which are used by the producers. These methods let us understand how the producers of manipulative messages which consist of manipulative speech acts apply to the recipients’ empathy and compassion. The results of such analysis show that the most frequently used linguistic means of realization of this manipulative strategy are nominating lexemes,associative lexemes and some stylistic means (anaphora, simile and some others). These results also let us conclude that using of ethological data in linguistics helps the researchers understand the mechanisms of linguistic manipulation in the British political discourse.